The Role of the Subdistrict Head in Guidance and Supervision of Village Asset Management in Telaga Antang, Kotawaringin Timur Regency, Central Kalimantan - Joko Ariyadi Setiawan; Hardiyanto Rahman (Sean Institute, 2026)
Village asset management is an important aspect in supporting effective, transparent, and accountable village governance. However, in practice, various problems are still found, particularly related to weak guidance and supervision by the subdistrict government. This study aims to analyze the role of the Subdistrict Head (Camat) in guiding and supervising village asset management in Telaga Antang, Kotawaringin Timur Regency. The research method used was a qualitative descriptive approach through observation, interviews, and document analysis. The results of the study indicate that the role of the Camat has not been optimal, as reflected in the limited guidance and supervision activities, weak cross-sector coordination, and ineffective implementation of monitoring and evaluation. The main problems encountered include limited human resources, inadequate facilities and infrastructure, budget constraints, difficult geographical conditions, and the low understanding of village officials regarding village asset management regulations. In addition, the implementation of digital systems such as SIPADES has not been fully effective due to infrastructure limitations and insufficient technical competence. Efforts made to address these problems include improving the capacity of village officials, strengthening inter-institutional coordination, developing standard operating procedures, and reinforcing regulations and budget support. This study also offers an innovation in the form of the Village Asset Order Movement (GERDAS-TAS) as a strategy to improve administrative orderliness, transparency, and accountability in village asset management. Therefore, optimizing the role of the Camat is key to realizing effective, accountable, and sustainable village asset governance in order to support the improvement of rural community welfare.